Providing a combined model of fuzzy AHP and numerical taxonomy analysis for sport organizational ranking and performance appraisal - Salimi, Mehdi; Khodaparast, Mahboubeh (International journal of system assurance engineering and management, 2019)
The aim of present study was to provide a combined model of fuzzy AHP and numerical taxonomy analysis for sport organizational ranking and performance appraisal in which subjects were Esfahan youth and sports offices (Iran). In the first step, related indices with four balanced scorecard perspective were identified, and scientific resources, research background, professional comments, and finally confirmatory factor analysis were used. Finally, 41 indices were identified and classified in four-perspectives balance scorecard (BSC). After confirmation of final construct of the BSC, fuzzy analytical hierarchy process was used to identify the weight of indices in every four perspectives. Then, in Esfahan, 26 youth and sports offices were ranked using numerical taxonomy method. According to the results, youth and sports offices of Esfahan city, Najafabad, and Shahinshahr were in first to third places, respectively. Finally, in order to conduct performance appraisal and rank sports organizations, a model was provided through the previous path. The provided model not only could identify studied organizations situation in every executive area but also could make a framework for better management and efficient performance.